2013
DOI: 10.1111/eth.12184
|View full text |Cite
|
Sign up to set email alerts
|

Antipredatory Response and Food Intake in Wood Mice (Apodemus sylvaticus) under Simulated Predation Risk by Resident and Novel Carnivorous Predators

Abstract: Chemical signals left by predators are a potential source of information about the risk of predation, and small mammals are known to take them into account when making decisions. We investigated whether wood mice (Apodemus sylvaticus) are more likely to avoid the faeces of resident predators (red fox Vulpes vulpes and common genet Genetta genetta) vs. a novel predator (European pine marten Martes martes). Odour recognition would increase perceived predation risk and reduce food intake by individual mice. Wood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 64 publications
0
36
0
Order By: Relevance
“…On the other hand, in summer months, mice become an essential element of the pine marten ( Martes martes ) diets (Rosellini, Barja, & Piñeiro, ; Rosellini, Barja et al., ; Rosellini, Osoria et al., ). Therefore, being the main prey of numerous predators implies that they have to adapt their behaviour to each particular situation, evaluating predation risk in order to perform the most suitable response (Navarro‐Castilla & Barja, ,b). Consequently, due to the influence of predation pressure, individuals seem to show conspicuously aggressive behaviour when they are intensely pursued.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, in summer months, mice become an essential element of the pine marten ( Martes martes ) diets (Rosellini, Barja, & Piñeiro, ; Rosellini, Barja et al., ; Rosellini, Osoria et al., ). Therefore, being the main prey of numerous predators implies that they have to adapt their behaviour to each particular situation, evaluating predation risk in order to perform the most suitable response (Navarro‐Castilla & Barja, ,b). Consequently, due to the influence of predation pressure, individuals seem to show conspicuously aggressive behaviour when they are intensely pursued.…”
Section: Discussionmentioning
confidence: 99%
“…In nature, animals must cope with a broad array of threats in order to survive and, among them, disturbance by humans poses crucial trade‐offs for wildlife populations. Direct and indirect impacts of anthropogenic interference cause wide‐ranging effects on wildlife affecting not only their ecology and, hence, population densities, but also shaping their behaviour and physiology (Barja et al., ; Borkowski et al., ; Davies, Haddad, & Ouyang, ; Fernández‐Juricic & Tellería, ; Johnson, Boyce, Schwartz, & Haroldson, ; Navarro‐Castilla & Barja, ,b; Stankowich, ). Several measures for evaluating human‐caused effects on wild populations have been used (Tarlow & Blumstein, ), but behavioural changes have been often considered the most sensitive measure of animal′s susceptibity to human effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same applies to rodents (Banks et al , Haapokoski et al ). In particular, wood mice are known to avoid areas frequented by predators (Díaz et al , Navarro‐Castilla and Barja ) as well as open microhabitats (Muñoz et al , Perea et al ). In fact, studies monitoring individual movements have found that home ranges shrink when exposure to predation increases (Tew and Macdonald , Tattersall et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Crows' ability to tailor their immediate response to the identity of the threat is supported by studies showing that animals such as breeding wood mice, Apodemus sylvaticus, and blue jays, Cyanocitta cristata, adjust subsequent foraging decisions to predator identity (Conover, 1979;Navarro-Castilla & Barja, 2013). That crows responded most strongly to a predator with a conspecific prey is consistent with a previous study on crows (Barash, 1976) and with responses by herring gulls, Larus argentatus, and lesser blackbacked gulls, Larus fuscus (Kruuk, 1976).…”
Section: Experiments 1: Crow Response To a Dead Conspecific And/or A Pmentioning
confidence: 99%